The Right not to Be Subjected to Enforced Disappearance Concept, Content and Scope - Pervou, Ioanna (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book offers a distinctive approach to the right not to be subjected to enforced disappearance. Over the last decade, the entry into force of the UN Convention for the Protection of All Persons from Enforced Disappearance has brought to the forefront of legal discussion the need to effectively address the practice of disappearance. Yet, there are still obstacles to combatting it, which are in part due to a limited understanding of the right's underlying concept, content and scope. This book examines the phenomenon and definition of enforced disappearance and sheds new light on the right against disappearance. Presenting a doctrinal appraisal of the norm's legal value, it suggests that the right against enforced disappearance holds a customary value, while also arguing that it has since attained a jus cogens status. Lastly, it examines in detail the rights to truth and reparation and how regional and national courts have interpreted these norms. It assesses the UN Convention's dynamics and considers whether the lack of a right against disappearance embedded in regional human rights systems affects individuals' protection. The book provides an overview of key jurisprudence on disappearances, making it of benefit to both practitioners and theorists of international law.
Introduction - The Concept of Enforced Disappearance -- The Content of Enforced Disappearance -- The Scope of the Right Not to Be Subjected to Enforced Disappearance -- The Scope of Truth and Reparation -- Conclusions.
Keywords: Human rights; Humanitarian law; International law; Peace; Law -- Philosophy; Law -- History; Human Rights; International Humanitarian Law, Law of Armed Conflict; Public International Law; Peace and Conflict Studies; Theories of Law, Philosophy of Law, Legal History